Improving genetic prediction by leveraging genetic correlations among human diseases and traits - Robert M. Maier (Nature Portfolio, 2018)
Genetic prediction of complex traits so far has limited accuracy because of insufficient understanding of the genetic risk. Here, Maier et al. develop an improved method for trait prediction that makes use of genetic correlations between traits and apply it to summary statistics of psychiatric diseases.